Peningkatan Kinerja Kelompok Tani Kelapa Sawit melalui Peran Penyuluh Pertanian di Desa Tebing Tinggi Pangkatan, Kecamatan Pangkatan, Kabupaten Labuhanbatu - Marihot, Marihot; Nasution, Ade Parlaungan; Siregar, Zulkifli Musannip Efendi (Universitas Galuh, 2024)
Farming improvement can be influenced by the presence of agricultural extension services in contributing knowledge (educator), creating ideas (innovator), instruction (facilitator), and mobilizer (motivator) for farmer groups. However, farmers' groups are not actively participating. This study was aimed to determine the relationship between agricultural extension services on the development of the oil palm farmer groups performance in Tebing Tinggi Pangkatan Village, Pangkatan Subdistrict, Labuhanbatu District. This study on sixteen farmer groups used descriptive methods with multiple linear regression and it was conducted from June to September 2023. Validity, reliability, classical assumption tests, statistical tests, and hypothesis testing were tested. The results showed that the agricultural extension services on the development of the oil palm farmer groups performance was classified as high (74.18%) and agricultural extension services as facilitators, innovators, motivators, and educators had a strong relationship (0.505; 0.680; 0.666, and 0.549) to the development of farmer group performance in this study.